Autoimmune Hepatitis A Guide for Practicing Clinicians - Hirschfield, Gideon M.; Heathcote, E. Jenny; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
With a focus on practical patient related issues, Autoimmune Hepatitis: A Guide for Practicing Clinicians serves as a useful practical, and much needed, resource for all those physicians presented with managing patients diagnosed with autoimmune hepatitis, both acutely and over the long term. It provides a basis for clinicians to understand the etiology of the disease, as well as special circumstances where management dilemmas often arise. Emphasis is given to providing management advice of immediate use to clinicians, something not presently offered by other larger general texts. The chapters are written by those with an expertise and training in this field and include the most up to date information. This book is of great value to Gastroenterologists, Hepatologists, and Internists at all levels who see patients presenting with autoimmune hepatitis.
Keywords: Medicine; Internal medicine; Gastroenterology; Clinical medicine; Medicine & Public Health; Gastroenterology; Hepatology; Internal Medicine